Factors controlling the development of phytoplankton blooms in the Antarctic Ocean — a mathematical model - Sakshaug, Egil; Slagstad, Dag; Holm-Hansen, Osmund (Marine Chemistry, 1991)
A mathematical model describing the development of phytoplankton blooms as a function of the depth of the wind-mixed layer, spectral distribution of light, passage of atmospheric low-pressure systems, size of the initial phytoplankton stock and loss rates is presented. Model runs represent shade-adapted, large-celled, bloom-forming diatoms. Periodic deep mixing caused by strong winds may severely retard the development of blooms and frequently abort them before macronutrients are completely exhausted. Moderate depths of mixing (40-50 m) in combination with a moderately large total loss rate (about 0.01 3 h-1) can prevent blooms from developing during the brightest time of the year. Complete exhaustion of macronutrients in the upper waters is likely only if the wind-mixed layer is less than 10 m deep, i.e. in very sheltered waters, and also in the marginal ice zone when ice is melting. We do not exclude the possibility of control of phytoplankton biomass by iron in ice-free, deep-sea parts of the Antarctic Ocean, but the implied enhancement of export production through addition of iron might be restricted because of limitation by light, i.e. vertical mixing.
Keywords: Scotiahavet; Sørishavet; fytoplankton; marin biologi; oseanografi

Microbial autotrophic and heterotrophic eucaryotes in Antarctic waters: relationships between biomass and chlorophyll, adenosine triphosphate and particulate organic carbon - Hewes, Christopher D.; Sakshaug, Egil; Reid, Freda M. H.; Holm-Hansen, Osmund (Marine Ecology Progress Series, 1990)
Microscopical examination of near-surface eucaryotic microbial populations in circumcontinental waters of Antarctica indicated that nanoplankton (<20 μm diameter) dominated in regions with low chlorophyll concentrations (< 1 μg l⁻¹). About 30 % of the mean nanoplankton carbon consisted of heterotrophic flagellates. Heterotrophic microplankton carbon (> 20 μm diameter) was generally less significant. The variation in phytoplankton biomass was the result primarily of changes in cell density of pennate diatoms in the East Wind Drift, and of centric diatoms in the Weddell Sea and the Scotia Ridge region. Autotrophic and heterotrophic carbon as determined by microscopical analysis were compared with data for total particulate carbon, chlorophyll a, and adenosine triphosphate. Estimates for the C:chl ratio of autotrophs increased with decreasing concentrations of chlorophyll a, with mean values of 46 in bloom waters and 144 in 'blue water'. A C:ATP ratio for heterotrophic nanoplankton was estimated to be about 100, while that for heterotrophic microplankton may be lower. Algorithms, incorporating concentrations of chlorophyll a and ATP, are described which allow estimates of autotrophic and heterotrophic microbial biomass.
Keywords: Sørishavet; alger; biomasse; fytoplankton; marin biologi; oseanografi; plankton; zooplankton

Effects of UV radiation on post-bloom phytoplankton populations in Kvalsund, North Norway - Walter Helbling, E.; Eilertsen, Hans Chr.; Villafañe, Virginia E.; Holm-Hansen, Osmund (Journal of Photochemistry and Photobiology B: Biology, 1996)
Our studies in the coastal waters in North Norway show that rates of photosynthesis of natural phytoplankton assemblages are strongly inhibited by solar UV radiation. When exposed to high irradiances of direct solar radiation, photosynthetic rates were increased by approximately 150% when all UV radiation was excluded from samples, with UVB radiation being responsible for approximately 50% of the total inhibition. There was no discernible threshold value for inhibition of photosynthesis by UV radiation, even at UV (280–400 nm) irradiances as low as 0.1 W m−2. When natural assemblages were incubated in situ, inhibition of photosynthetic rates were detectable down to 10 m, where solar irradiance was about 3% of the radiation incident on the sea surface. Based on the inhibition of photosynthetic rates at very low fluences of UV radiation, post-bloom assemblages of phytoplankton in North Norway and possibly also in the Arctic ocean appear to be more sensitive to solar UV radiation than phytoplankton from the Southern Ocean.
Keywords: Sørishavet; fotosyntese; fytoplankton; marin biologi; polarområdene; ultrafiolett stråling